2017
DOI: 10.1093/cercor/bhx057
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role of Inhibition in Temporal Processing Maturation in the Primary Auditory Cortex

Abstract: Faithful representation of sound envelopes in primary auditory cortex (A1) is vital for temporal processing and perception of natural sounds. However, the emergence of cortical temporal processing mechanisms during development remains poorly understood. Although cortical inhibition has been proposed to play an important role in this process, direct in-vivo evidence has been lacking. Using loose-patch recordings in rat A1 immediately after hearing onset, we found that stimulus-following ability in fast-spiking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…This higher variability may be related to the stochastic nature of neural responses, which may reduce with neural maturation. This reduction with age might arise because of progressive increase in neural inhibition and decrease in spontaneous neural activity in auditory brain structures over development (Babola et al, 2018;Cai et al, 2017;Wang & Bergles, 2015). Decrease of internal noise levels with age could also relate to progressive decrease in random fluctuations of selective auditory attention capacities (Jones et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This higher variability may be related to the stochastic nature of neural responses, which may reduce with neural maturation. This reduction with age might arise because of progressive increase in neural inhibition and decrease in spontaneous neural activity in auditory brain structures over development (Babola et al, 2018;Cai et al, 2017;Wang & Bergles, 2015). Decrease of internal noise levels with age could also relate to progressive decrease in random fluctuations of selective auditory attention capacities (Jones et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The initial reports that GABAergic synapses are plastic suggested that ISP contributes to cortical circuit refinement (Komatsu & Iwakiri, 1993;Maffei et al, 2004Maffei et al, , 2006 and possibly learning (Buzsaki, 1997;Kano, 1995;Nugent, Penick, & Kauer, 2007). Since these pioneering studies, experimental work demonstrated that changes in inhibitory synaptic efficacy are associated with adaptation of olfactory responses in drosophila (Das et al, 2011), with changes in sensory experience (Cai et al, 2018;D'Amour & Froemke, 2015;House et al, 2011;Maffei et al, 2004Maffei et al, , 2006, fear conditioning (Letzkus et al, 2011;Lucas, Jegarl, Morishita, & Clem, 2016;Xu et al, 2014) and exposure to drugs of abuse (Dacher & Nugent, 2011;Nugent et al, 2007). The specific mechanisms by which ISP contributes to learning and memory are only beginning to being unravelled.…”
Section: Synaptic Plasticit Y Learning and Memorymentioning
confidence: 99%
“…GABA A receptor blockade results in cortical neuron responses at lower sound levels, to a broader range of sound levels, to a broader range of modulation rates, and to a broader range of stimulus durations (Chen and Jen, 2000;Wang et al, 2002Wang et al, , 2016Razak and Fuzessery, 2009). Specific manipulations of FS parvalbumin-positive interneurons or low threshold spiking somatostatin-positive interneurons, suggest that FS cells provide temporally precise feedforward inhibition to auditory cortical pyramidal neurons (Hamilton et al, 2013;Li et al, 2014Li et al, , 2015Natan et al, 2017;Cai et al, 2018;Keller et al, 2018;Liu et al, 2019). Together, these observations suggest that the strong FS inhibition contributes to the temporal following ability of pyramidal neurons.…”
Section: Relationship Between Synaptic and Behavioral Findingsmentioning
confidence: 99%